La Phrygie Paroree et la Pisidie septentrionale aux epoques hellenistique et romaine : geographie historique et sociologie culturelle - Bru, Hadrien (Koninklijke Brill, 2017)
"La Phrygie Parorée et la Pisidie septentrionale deals with the history, the historical geography and the cultural sociology of Phrygia Paroreios and northern Pisidia during the Hellenistic and Roman periods (IVth cent. BC-IVth cent. AD). This region of inner Anatolia, mostly inhabited by Pisidians and Phrygians, faced gradually the settlement of Greek, Macedonian, Jewish, Thracian, Lycian and Roman colonists who deeply modified the local cultures and geopolitics. With an approach based on epigraphic, archaeological, literary and numismatic sources, this work is the first historical synthesis devoted to a region showing strong cultural identities, which makes it essential to the understanding of the Graeco-Roman East"--Publisher description.
Keywords: Phrygia -- Antiquities.; Pisidia -- Antiquities.; Phrygia -- History -- Sources.; Pisidia -- History -- Sources.; Phrygia -- Historical geography.; Pisidia -- Historical geography.; Cultural pluralism -- Turkey -- Phrygia -- History.; Cultural pluralism -- Turkey -- Pisidia -- History.; Social change -- Turkey -- Phrygia -- History.; Social change -- Turkey -- Pisidia -- History.; Diversité culturelle -- Turquie -- Pisidie -- Histoire.; HISTORY -- Ancient -- General.; Antiquities; Cultural pluralism; Historical geography; Social change; Asia -- Phrygia; Mediterranean Region -- Pisidia; History; Sources